2010
DOI: 10.1002/oti.291
|View full text |Cite
|
Sign up to set email alerts
|

A client‐centred, occupation‐based occupational therapy programme for adults with psychiatric diagnoses

Abstract: The purpose of this study was to assess the effectiveness of a client-centred, occupation-based occupational therapy programme for individuals with psychiatric diagnoses. The study took place in a college campus. A pre-test/post-test design was used. There were 38 participants which included college students and community members who desired to attend college, work and/or address life skill goals. The Canadian Occupational Performance Measure (COPM) was used as a pre- and post-test measure. Goals were based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 17 publications
2
22
0
4
Order By: Relevance
“…An occupation-based practice uses occupation throughout the OT therapeutic process of assessment, intervention, and measurement of outcome (6). Client-centered and occupation-based are an inter-reliant approach in OT that has yielded greater client satisfaction and success in occupational performance (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…An occupation-based practice uses occupation throughout the OT therapeutic process of assessment, intervention, and measurement of outcome (6). Client-centered and occupation-based are an inter-reliant approach in OT that has yielded greater client satisfaction and success in occupational performance (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…A study in adult clients with mental illness found that OBI increases occupational performance and satisfaction (17). OBI is also effective in minimizing the decline in leisure and ADLs engagement (18).…”
mentioning
confidence: 99%
“…Outros estudos analisaram a clientela com transtornos psiquiátricos, evidenciando que, embora seja um desafio, o COPM pode ser aplicado satisfatoriamente, sendo importante analisar as diferenças entre os julgamentos dos clientes e o desempenho real, bem como avaliar a viabilidade da Prática Clínica Centrada no Cliente (PAN et al, 2003;SCHINDLER, 2010). Entende-se que embora possa haver divergências entre o que é percebido pelo terapeuta e o que é exposto pelo cliente, a abordagem é realizada baseada na perspectiva do que é significativo para o sujeito.…”
Section: Resultsunclassified